Like iron in the blood of the people: the requirement for heme trafficking in iron metabolism - Korolnek, Tamara; Hamza, Iqbal (Frontiers in Pharmacology, 2014)
Heme is an iron-containing porphyrin ring that serves as a prosthetic group in proteins that function in diverse metabolic pathways. Heme is also a major source of bioavailable iron in the human diet. While the synthesis of heme has been well-characterized, the pathways for heme trafficking remain poorly understood. It is likely that heme transport across membranes is highly regulated, as free heme is toxic to cells. This review outlines the requirement for heme delivery to various subcellular compartments as well as possible mechanisms for the mobilization of heme from these compartments. We also discuss how these trafficking pathways might function during physiological events involving inter- and intra-cellular mobilization of heme, including erythropoiesis, erythrophagocytosis, heme absorption in the gut, as well as heme transport pathways supporting embryonic development. Lastly, we aim to question the current dogma that heme, in toto, is not mobilized from one cell or tissue to another, outlining the evidence for these pathways and drawing parallels to other well-accepted paradigms for copper, iron, and cholesterol homeostasis.